2017
DOI: 10.12659/msm.903188
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Vaccination against Streptococcus Pneumoniae in Cochlear Implant Patients

Abstract: BackgroundStreptococcus pneumoniae can cause life-threatening illness, with invasive pneumococcal diseases (IPD) like meningitis, sepsis, bacteremic pneumonia, and bacteremia being major causes of morbidity and mortality. Studies have shown that patients who have had a cochlear implant, particularly children, have an increased risk of bacterial (pneumococcal) meningitis. Vaccination in patients with cochlear implants is important and recommended universally. The World Health Organization recommends the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…This is considerably lower than the state and national standard immunisation schedule uptake average of >91% 12 . However, it is consistent with medically at‐risk paediatric pneumococcal vaccine coverage reported at 3–9% nationally, 13 and other international adult and paediatric CI cohorts in Poland (28%) 14 and America (20%) 15 . Locally, educational letters and immunisation plans for children scheduled for or who had received CI were effective in improving immunisation rates (Tay SM, unpublished data), suggesting improved parent and provider awareness were key factors influencing optimal infection prevention.…”
Section: Discussionsupporting
confidence: 70%
“…This is considerably lower than the state and national standard immunisation schedule uptake average of >91% 12 . However, it is consistent with medically at‐risk paediatric pneumococcal vaccine coverage reported at 3–9% nationally, 13 and other international adult and paediatric CI cohorts in Poland (28%) 14 and America (20%) 15 . Locally, educational letters and immunisation plans for children scheduled for or who had received CI were effective in improving immunisation rates (Tay SM, unpublished data), suggesting improved parent and provider awareness were key factors influencing optimal infection prevention.…”
Section: Discussionsupporting
confidence: 70%
“…Piotrowska et al observed a 49.2 per cent streptococcal pneumonia vaccination rate despite the vaccine being mandatory and publicly funded for cochlear implant patients in Poland. 16 A recent Spanish study showed that only 5.71 per cent of the cochlear implant patients had 100 per cent compliance to their vaccination schedule. Their paediatric population had pneumococcal conjugate and H influenzae B vaccine compliance rates of more than 90 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…Pnömokok enfeksiyonları açısından risk faktörüne sahip bireylere 23 serotip içeren polisakkarit aşı da önerilmektedir. Ancak koklear implant yapılmış 2628 çocuk ve erişkin hastanın incelendiği bir çalışmada pnömokok aşısı yapılma oranının çocuklarda %49.2, erişkinlerde ise sadece %5.5 olduğu görülmüştür 10 . Koklear implant yapılmış toplam 1222 hastada üç menenjit olgusunun görüldüğü çalışmada pnömokok aşılama durumu ile menenjit gelişimi arasında ilişki bulunmamıştır 6 .…”
Section: Discussionunclassified